Ortho-preventive approach to early loss of the deciduous second molar: case report (Research, Society and Development, 2021)
Objective: The objective of this work was to recover a lost tooth space as a result of early loss of the second primary molar. In the approach, a removable space stove was used and finished with segmented fixed appliance. As a result, full recovery of space and physiological eruption of the impacted premolar were observed, emphasizing the importance of preventive and interceptive orthodontics in the correction of early diagnosed malocclusion. Methodology: Based on the patient's permission through the Free and Informed Consent Term to share their image for the proper purpose, this study is a clinical case report of descriptive analytical nature (Pereira et al., 2018). Case report: A 9-year-old male patient presented with a Class II right dental subdivision 1 malocclusion of Angle, due to early loss of element 55 (deciduous upper right second molar). The treatment proposed the installation of a removable space recovery device, which was necessary to replace it throughout the treatment with a segmented fixed device with a finger clip due to the COVID-19 pandemic, in order to accelerate the recovery of the space and take advantage of the greater eruptive force of the dental element. Conclusion: The resources offered with the use of space recovery devices are effective in intercepting and treating early diagnosed malocclusions.